Güncel Biyokimya Çalışmaları VII (Bahar) - Atıcı, Yasemin; Ökten, Zeynep; Kasebi, Sara; Semerci Arıkan, Buse; Erdem, Mehmet; Kıran, Tuğba Raika; Yağız, Abdullah Kaan; Aktolun, Berat; Güvenç Demirağcı, Yeşim; Kara, Hatibe; Gök, Gamze; Elbaş, Yavuz; et al. (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-